SPIRITUAL TEACHING DALAM PEMBELAJARAN IPA DI MADRASAH - Mahmudah, Laely (Program Studi Pendidikan Agama Islam, 2016)
SPRITUAL TEACHING IN SCIENCE LEARNING IN MADRASAH. The purpose of national education must be realized in a series of learning process. One of the ways to realize it is by applying the spiritual teaching. Spiritual teaching is teaching and guiding the learners by instilling values and religious spirit which is integrated in knowledge and skill concept in accordance with the learning purposes. The essence of science learning includes four main elements. They are attitude, process, product, and application. Spiritual teaching in science learning in madrasah can be implemented in some ways, some of them are: 1) reflective learning, 2) contextual learning (CTL), 3) spiritual educational game (SEG), and 4) outdoor learning. The teacher is able to choose the learning method that will be applied. It is associated with the material that will be delivered. When the teacher applies the spiritual teaching in science learning in madrasah, it is hoped that the students will be smart comprehensively, intellectually, spiritually, and emotionally/socially.